Financial knowledge as an endogenous source of the LGUs' potential - Tomasz Wolowiec (e-Finanse: Financial Internet Quarterly, 2012)
Financial knowledge is an extremely important element not only of functioning and development, but more importantly of managing financial processes at local government level. Considering the progressing reforms of the national public finance system and the resulting consequences (legal, financial, as well as managerial) for shaping the financial management of the LGU's, and also globalisation processes and the dynamic development of the financial services' market, it is natural to require managers of the local government subsector of public finance to have thorough financial knowledge - current and interdisciplinary knowledge that would most importantly be reliable and practice-based. Constant changes of regulations, growing demands in budget management, progressing restrictions as concerns LGUs' debt-raising capacity require not only current, static financial knowledge expected when executing statutory tasks, but also dynamic knowledge based on strategic planning, i.e. knowledge based on modern financial instruments.
Keywords: G0; G14; H75; H76; 330; LGU's; financial knowledge; potential; organisational learning; financial instruments